Phage Origin of Mitochondrion-Localized Family A DNA Polymerases in Kinetoplastids and Diplonemids. (11th January 2021) - Harada, Ryo; Inagaki, Yuji
Abstract: Mitochondria retain their own genomes as other bacterial endosymbiont-derived organelles. Nevertheless, no protein for DNA replication and repair is encoded in any mitochondrial genomes (mtDNAs) assessed to date, suggesting that the nucleus primarily governs the maintenance of mtDNA. As the proteins of diverse evolutionary origins occupy a large proportion of the current mitochondrial proteomes, we anticipate finding the same evolutionary trend in the nucleus-encoded machinery for mtDNA maintenance. Indeed, none of the DNA polymerases (DNAPs) in the mitochondrial endosymbiont, a putative α-proteobacterium, seemingly had been inherited by their descendants (mitochondria), as none of the known types of mitochondrion-localized DNAP showed a specific affinity to the α-proteobacterial DNAPs. Nevertheless, we currently have no concrete idea of how and when the known types of mitochondrion-localized DNAPs emerged. We here explored the origins of mitochondrion-localized DNAPs after the improvement of the samplings of DNAPs from bacteria and phages/viruses. Past studies have revealed that a set of mitochondrion-localized DNAPs in kinetoplastids and diplonemids, namely PolIB, PolIC, PolID, PolI-Perk1/2, and PolI-dipl (henceforth designated collectively as "PolIBCD+") have emerged from a single DNAP. In this study, we recovered an intimate connection between PolIBCD+ and the DNAPs found in a particular group of phages. Thus, the common ancestor of kinetoplastids and diplonemids most likely converted a laterally acquired phage DNAP into a mitochondrion-localized DNAP that was ancestral to PolIBCD+. The phage origin of PolIBCD+ hints at a potentially large contribution of proteins acquired via nonvertical processes to the machinery for mtDNA maintenance in kinetoplastids and diplonemids.